Performance Analysis of Spatial Channel Model in fast Fading - Srivastava, Sandeep (My University, 2010)
Future wireless communication systems will utilize the spatial properties of the wireless channel to improve the spectral efficiency and thus increase capacity. This is realized by deploying multiple antennas at both the transmitter and receiver. Development and analysis of communication systems utilizing the spatial properties of the channel requires channel models that properly reflect these characteristics. Due to the unpredictable nature of the wireless channel, a common approach is to model its effects statistically. A few large world-wide cooperations, like the third generation partnership project (3GPP) have developed channel models intended for reference and standardization use. These models are partly based on some bulk parameters that describe the characteristics of the channel over larger areas of several wavelengths. Such parameters include shadow fading, angle spread, and delay spread, etc. In the spatial channel model (SCM) these large-scale parameters are, however, assumed independent between separate links, i.e., between channels modelling the propagation between one mobile and several base stations, or between one base station and several mobiles. Such assumptions may be valid for single-link, singe-cell systems, where each communication link is sufficiently separated in either time or frequency. In practice, dependencies between parameters describing separate wireless channels is expected. Future systems will allow a dense frequency reuse, and results from system evaluations based on models with independent links may be inaccurate. Examples of this may be in systems that exploit the spatial nature of the channel, like multi-user scheduling using a single carrier, or macro-diversity systems deploying several base stations. Therefore, it is important to analyze multi-node measurements in order to extract and characterize this channel dependence. The aim of this thesis is to investigate MIMO system capacity using the Spatial Channel Model (SCM) and Channel Fast Fading, Channel Capacity, Spatial Autocorrelation, Power delay profile for different channel environments, proposed by standardization bodies (3GPP-3GPP2) for third generation systems. In principle, the MIMO systems capacity can increase linearly with the number of antennas. In this thesis, system model for investigating the MIMO system is ﬁrst summarized. The capacity of MIMO systems in SCM propagation scenarios (suburban macro-cell and urban micro cell) is then evaluated and compared with i.i.d. model results. The simulation results show that capacity of the more realistic SCM channels does not increase linearly with the number of antennas. Analyses on channel capacity variation with time, variation in spatial auto- correlation with time and its power delay profile have done.
M.E. (ECED)
Keywords: MIMO; SCM; 3GPP